2019
DOI: 10.3390/molecules24061032
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and DNA Fingerprinting of Griffonia simplicifolia Baill.

Abstract: Background: Griffonia simplicifolia Baill. (Caesalpiniaceae) is a medicinal plant whose seeds are widely used in traditional medicine for their high content of 5-hydroxy-l-tryptophan (5-HTP), a direct precursor and enhancer of the activity of the brain hormone serotonin (5-HT). The plant extracts are used in dietary supplements aimed to alleviate serotonin-related disorders. Methods: In order to characterize the chemical components of G. simplicifolia seeds and their identity, we used a combined methodology by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…Phytochemical studies indicated the presence of glycosides, tannins, flavonoids, alkaloids, saponins and coumarins in the leaf extract of the plant [33]. In the seed, many authors have also found lectins 5-hydroxy-L-tryptophan (5-HTP) a direct precursor in the synthesis of serotonin (5-HT) and fatty acids [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical studies indicated the presence of glycosides, tannins, flavonoids, alkaloids, saponins and coumarins in the leaf extract of the plant [33]. In the seed, many authors have also found lectins 5-hydroxy-L-tryptophan (5-HTP) a direct precursor in the synthesis of serotonin (5-HT) and fatty acids [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Fingerprint techniques, including DNA molecular fingerprint [44] and chemical fingerprinting [45], are crucial for assessing quality of commercial products, and give information about the purity of the original raw material. DNA molecular fingerprinting cannot be applied to the major part of extracts made with organic solvent, due either to the insolubility of nucleic acids in extraction solvents or to DNA instability during manufacture procedures.…”
Section: Chemical Fingerprinting Of the 24 V Macrocarpon-based Dietamentioning
confidence: 99%
“…Serotonin (5-hydroxytryptamine) is one of the main neurotransmitters that regulate brain function. Tryptophan hydroxylase (TPH) catalyzes the rate-limiting step of serotonin biosynthesis from 5-hydroxy- l -tryptophan (5-HTP) [ 90 , 91 ]. The extract of the Griffonia simplicifolia Baill has been found to contain large amounts of 5-HTP.…”
Section: Serotonin: Physiological Role In the Pathogenesis Of Alzhmentioning
confidence: 99%
“…The extract of the Griffonia simplicifolia Baill has been found to contain large amounts of 5-HTP. This, according to the authors of this study, makes it possible to recommend the specified plant extract for the complex treatment of neurodegenerative diseases associated with impaired serotonin synthesis [ 90 ]. In addition, there is evidence that tryptophan metabolites may have neuroprotective effects in AD.…”
Section: Serotonin: Physiological Role In the Pathogenesis Of Alzhmentioning
confidence: 99%